Parenting Education as Efforts to Improve Parents' Knowledge in Guiding Children with Special Needs Study at Home - Aqmar, Ami Hamimi Zatil; Maryanti, Rina; Rusyani, Endang; Wulandary, Verra (JASSI ANAKKU, 2020)
Seeing the difficulties faced by parents in guiding their children to study at home, especially children with special needs, parenting education is an effort to increase parents' knowledge about the guidance of children with special needs studying at home is very important. It aims to provide solutions to the various problems experienced by parents so that they are able to carry out their role in guiding children with special needs to study well at home. The subjects of this study were parents of students from a school in West Java. The activity carried out was the provision of material on guiding children with special needs to study at home through whatsapp media which was presented in the form of microblogs and PDFs. The conclusion of this study is that parents gain new knowledge about guiding children with special needs to study at home.